2018
DOI: 10.3389/fpubh.2018.00187
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Conceptualization and Resilience Factors in the Kalasha Youth: An Indigenous Ethnic and Religious Minority Community in Pakistan

Abstract: The Kalasha are a religious, ethnic, and linguistic minority community in Pakistan. They are indigenous people living in remote valleys of the Hindu Kush Mountains in northern Pakistan, neighboring Afghanistan. The Kalasha are pastoral, as well as agricultural people to some extent, although they are increasingly facing pressures from globalization and social change, which may be influencing youth and community development. Their traditional world view dichotomizes and emphasizes on the division of the pure (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Likewise, low mental literacy is the cause of abuse in mental health care facilities which results in restraining or chaining patients with mental disorders (Michael et al, 2012). Since the last few years, mental health has remained a subject of debate in Pakistan (Naz and Khalily, 2016;Choudhry and Bokharey, 2013;Choudhry et al, 2017Choudhry et al, , 2018. In the background of growing terrorism, insecurity, constant poverty, stress, unemployment and disruption of the social fabric, the incidence and prevalence of mental health issues have increased tremendously (Gadit and Vahidy, 1999;Choudhry et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, low mental literacy is the cause of abuse in mental health care facilities which results in restraining or chaining patients with mental disorders (Michael et al, 2012). Since the last few years, mental health has remained a subject of debate in Pakistan (Naz and Khalily, 2016;Choudhry and Bokharey, 2013;Choudhry et al, 2017Choudhry et al, , 2018. In the background of growing terrorism, insecurity, constant poverty, stress, unemployment and disruption of the social fabric, the incidence and prevalence of mental health issues have increased tremendously (Gadit and Vahidy, 1999;Choudhry et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Pakistan, the budget fixed for mental health is less than 2 percent (Afridi, 2008;Rathod et al, 2017). Due to a limited number of psychiatrists and psychologists (one psychiatrist is hired for more than 10,000 people), poor conditions/facilities of Basic Health Units (BHU), the majority of patients visit traditional faith healers (Choudhry and Bokharey, 2013;Choudhry et al, 2017Choudhry et al, , 2018Choudhry, Munawar, Akram, Al-Worafi, Bakrin, Tey, Jacob, Hing, Khan, Han and Kamal, 2019;Akbari et al, 2009). According to an estimate, there are a total of 203.07 (per 100,000 populations) professionals offering services in various mental health institutes either privately or under government practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the evolutionary biological study of cooperation, it is widely accepted that humans cooperate in a wide variety of ways and on large scales (Townsend, Aktipis, Balliet & Cronk, 2020). The empirical shred of evidence also found that generosity, life-management skills, and social selfefficacy beliefs play an important in promoting ones' goodness towards life in general especially when it comes to their interest and belief in activities for the common good (Van Dyke, et, al., 2009); Koenig, 2012; Choudhry, et al, 2018). As the youth gets more and more involved in interpersonal generosity it fosters their resiliency to combat stressors of life due to the remarkable benefits they earned for attaining spiritual wealth and mental health.…”
Section: Discussion/analysismentioning
confidence: 99%
“…The interview-based methods are famous in health-care studies and semistructured interviews are usually based on a flexible topic guide that offers a loose structure of open-ended questions to explore experiences and attitudes. 1924 Especially when some urgent assessment is required for a public health problem, the studies based on social media trending are beneficial for policymakers and help to plan some immediate interventions. This analysis covers a broad range of analytic approaches (e.g., intuitive, impressionistic, interpretive analyses, as well as strict textual and systematic analyses).…”
Section: Discussionmentioning
confidence: 99%